Distribution patterns of oceanic micronekton at seamounts and hydrographic fronts of the subtropical Atlantic Ocean - Diekmann, Rabea (2004)
In the past the oceanic environment has often been compared with terrestrial deserts and until today relatively little is known about the ecology of the high seas. Within the present study pelagic oceanic communities of cephalopods and fish in the subtropical North Atlantic were investigated, and it was analysed at different spatial scales how these communities varied in response to physical gradients and hydrographic processes. First, the influence of the subtropical convergence zone in the Sargasso Sea on the distribution of early life stages of cephalopods was determined. This large-scale front turned out to represent a distinct faunal boundary, with higher diversity and abundance values in the northern part of the Sargasso Sea compared to the southern area. Second, mesoscale distribution patterns of paralarval cephalopods and larval fish were described at Great Meteor Seamount in relation to the specific hydrographic features, as e.g. the Taylor cap. Processes structuring the pelagic communities were identified and their impact evaluated by different multivariate statistical techniques. Fish and cephalopods were similarly influenced, although the retention potential at the seamount was much more pronounced for larval fish. Third, the diurnal vertical migration behaviour of juvenile and adult cephalopods was investigated from samples collected at three seamounts of different topographic morphology. A logistic regression model was developed to demonstrate the probability of occurrence in relation to daytime and catch depth. Because of the species-specific vertical distribution the seamounts represented a topographic obstacle, resulting in an impoverished fauna at shallower water depth.